Comparative Evaluation of Antimicrobial Efficacy of Contemporary and Novel Intracanal Medicaments against Enterococcus Faecalis - An In-vitro Study - Divya Singh; Gaurav Jain; Pradyumna Misra; Preeti Shukla; Sheetal Verma (Journal of Pharmacy and Bioallied Sciences)
Background: Endodontic treatment aims to preserve compromised teeth by eliminating microorganisms from the root canal system. Persistent root canal infections, especially those involving Enterococcus faecalis (E. faecalis), can lead to treatment failure. This study evaluates the antimicrobial efficacy of both traditional and novel intracanal medicaments against E. faecalis. Materials and Methods: The study employed an in-vitro design to assess the antimicrobial efficacy of various intracanal medicament combinations against E. faecalis (ATCC 29212). The medicaments tested included 2% Chlorhexidine (CHX) combined with Alexidine, Calcium Hydroxide (Ca(OH)2), Metronidazole, and Silver Nanoparticles (AgNPs). Antimicrobial activity was determined using the disc diffusion method, and the zone of inhibition (ZOI) was measured at 24, 48, and 72 hours. Results: Group 1 (2% CHX + Alexidine) and Group 5 (2% CHX + Ca(OH)2) showed the highest initial antimicrobial efficacy at 24 hours, with mean ZOIs of 18.16 mm and 18.09 mm, respectively. At 48 and 72 hours, Group 4 (2% CHX + AgNPs) exhibited the highest efficacy with a mean ZOI of 16.17 mm. Statistical analysis showed significant differences between groups at all time intervals (P < 0.05). Conclusion: The combination of traditional and novel intracanal medicaments, specifically CHX with Alexidine and CHX with AgNPs, significantly enhanced antimicrobial efficacy against E. faecalis. The combination of CHX and Alexidine demonstrated the highest initial activity, while CHX and AgNPs provided sustained antimicrobial effects.